2000
DOI: 10.1039/a909450d
|View full text |Cite
|
Sign up to set email alerts
|

Electronic substituent effect on intramolecular CH/π interaction as evidenced by NOE experiments

Abstract: In order to demonstrate the hydrogen-bond-like character of the CH/π interaction, electronic substituent effects on the equilibria between the stretched and the folded conformers of series of compounds capable of forming CH/π interactions were examined by measurements of NOE enhancements of 1 H NMR signals. Nuclear Overhauser enhancement is shown to be useful to determine the abundance of the CH/π proximate folded conformer. The Hammett plots of all series of the compounds capable of having CH/π interaction ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 48 publications
4
45
0
1
Order By: Relevance
“…The close proximities of CH 3 of the alkoxylic groups to phenyl and the π-shielding agree with the results of Nishio et al,8,9 although they may be directed by the electronic delocalization and interactions of the keto and ester groups with phosphorus rather than by C H/π interactions. There should be a favorable interaction between a keto oxygen and a phosphonium ion in 1 (refer to Scheme 1) where, in the crystal, the P .…”
Section: O As Hydrogen Bond Donors/acceptors 15 (Seesupporting
confidence: 83%
See 1 more Smart Citation
“…The close proximities of CH 3 of the alkoxylic groups to phenyl and the π-shielding agree with the results of Nishio et al,8,9 although they may be directed by the electronic delocalization and interactions of the keto and ester groups with phosphorus rather than by C H/π interactions. There should be a favorable interaction between a keto oxygen and a phosphonium ion in 1 (refer to Scheme 1) where, in the crystal, the P .…”
Section: O As Hydrogen Bond Donors/acceptors 15 (Seesupporting
confidence: 83%
“…These structures allow π-shielding of CH 3 of the alkoxylic groups due to their directed orientations, with the possibility of mildly favorable C H/π interactions. 8, 9 Interactions with solvents used in crystallizations appear not to affect conformations in the crystal 3,4 or in solution (see Tables III and IV), although CHCl 3 is a hydrogen-bond donor and DMSO interacts with cationoid centers. 15 Structures of 2 and 3 optimized by using the HF 3-21 (G * ) and 6-31 (G * ) basis sets are similar to those in the crystal.…”
Section: Discussionmentioning
confidence: 92%
“…57 Though the CHAp bond is weak, still it is known to lie within the lower end of the hydrogen bonding regime. 58 The electron withdrawing tendency of CH carbon and electron donating tendency of p aromatic system are known to play a significant role in multiple interactions. 57 Suezawa et al 56 studied the importance and effectiveness of the aromatic CH-p hydrogen bond for complex cluster formation.…”
Section: Resultsmentioning
confidence: 99%
“…Though weak, the CH/π hydrogen bond plays significant roles in various fields of chemistry such as the conformation of molecules, [12] selfassembly [13] as well as chiral recognition. [14] The electronic substituent effect on the stereoselectivity of complex formation, [15] conformational equilibrium, [16] crystal packing, [17] and enantioselectivity [18] has demonstrated that the CH/π interaction is by no means merely a dispersion force. According to high-level ab initio calculations, the most important stabilization comes from the correlation energy.…”
Section: Introductionmentioning
confidence: 99%